A novel role of HIF-1α/PROX-1/LYVE-1 axis on tissue regeneration after renal ischaemia/reperfusion in mice. (8th August 2019) - Meng, Fanwei
Abstract: Context: Renal ischaemia reperfusion (I/R) is a common clinical condition with a high morbidity and mortality rate. To date, I/R-induced renal injury remains an ineffective treatment. Objective: We hypothesis that angiogenesis and lymphangiogenesis markers, prospero homeobox-1 (PROX-1) and lymphatic endothelial hyaluronan receptor-1 (LYVE-1), are critical during I/R. Material and methods: Kunming mice were subjected to I/R and observed for the following eight consecutive days. Pathology analysis and protein distribution were detected by H&E staining, immunohistochemistry and immunofluorescence confocal analysis. Results: After I/R treatment, renal pathology was changed. HIF-1α was induced in the early stage and colocalisation with PROX-1 mainly in the renal tubular region, whereas PROX-1 and LYVE-1 were colocalised in the glomerulus of the endothelial region. Conclusions: In this study, we revealed HIF-1α/PROX-1/LVYE-1 axis dynamic changes in different regions after I/R and demonstrated for the first time it activates during I/R repair.